Faktor yang Mempengaruhi Kejadian Demam Berdarah Dengue Berdasarkan Model Spasial di Kabupaten Sikka Tahun 2019-2021 - Anastasia Sofia Lete Keraf; Pius Weraman; Honey Ivon Ndoen; Yendris Krisno Syamruth (JURNAL BIDANG ILMU KESEHATAN, 2023)
Various efforts to control dengue cases in Sikka Regency have been carried out, one of which was by issuing a Regent's Instruction in 2019 but cases increased by 1,816 cases from 620 cases in 2019. In 2020 another Regent's Instruction was issued so that dengue cases decreased to 183 cases. There are many risk factors for increasing dengue cases that have not been detected. One way is to look at the risk factors for dengue fever from a regional (spatial) perspective. Sikka Regency has experienced 4 outbreaks in the period 2010-2021. The study aims to analyze the factors that influence the incidence of DHF studied in the spatial analysis model. Type of research is analytic observational with an ecological study design. The data used in this study is secondary data. The results showed that there was an effect of population density in 2020 on the incidence of DHF, while population density in 2019 and 2021 had no effect. There are 6 sub-districts that become hotspot areas (High-High) in the influence of population density with DHF, namely Nelle, Kewapante, Kangae, Alok, East Alok and Lela Districts, while the coldspot (Low-High) areas are East Alok and Koting Districts. The altitude of the area has no effect on the incidence of DHF in 2019-2021. There are 2 hotspots, namely Nelle and Koting sub-districts, while the coldspot areas are in Kewapante, Alok Timur, Kangae and Lela sub-districts. There is no effect of temperature, humidity and rainfall in 2019, whereas in 2020 humidity has a positive effect and rainfall has a negative effect on the incidence of DHF and in 2021 there is a positive effect of air humidity on the incidence of DHF in Sikka Regency. Suggestions for dengue prevention programs need to be prioritized in hotspot and coldspot areas. There needs to be an alert for DHF in neighboring areas of DHF outbreaks. Keywords : Aedes Aegypti, Moran’s I, LISA, Autocorrelation spatial, Spatial regression